Esforços máximos em pontes tipo grelha - Longo, Henrique Innecco (1979)
The scope of this work is the determination of the maximum forces in highway bridges, by a computer program. The bridge superstructure is composed by a grid which can be orthogonal, skew, simply supported or continuous. The searching of the unfavorable vehicle position is done by a direct search method, considering the influence surfaces concept. The surface's ordinates in the interior grid, are obtained by a interpolation function. The program gives the maximum bending moments due to moving loads and the transversal distribution coefficients, which can be utilized in the determination of maximum shear forces.